Emotion in Social Relations : Cultural, Group, and Interpersonal Perspectives. - Parkinson, Brian, 1958- (Psychology Press, 2005)
Within psychology, emotion is often treated as something private and personal. In contrast, this book tries to understand emotion from the 'outside, ' by examining the everyday social settings in which it operates.